2022
DOI: 10.18632/oncotarget.28169
|View full text |Cite
|
Sign up to set email alerts
|

The androgen receptor inhibits transcription of GPER1 by preventing Sp1 and Sp3 from binding to the promoters in prostate cancer cells

Abstract: G-1, a GPER1 agonist, was shown to inhibit the growth of castration-resistant mouse xenografts but not their parental androgen-dependent tumors. It is currently unknown how the androgen receptor (AR) represses GPER1 expression. Here, we found that two GPER1 mRNA variants (GPER1v2 and GPER1v4) were transcriptionally repressed, not via transcript destabilization, by the androgen-activated AR. Although no AR binding was found in all active promoters near GPER1, data from promoter assays suggested that both varian… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
0
3
0
Order By: Relevance
“…We next investigated the molecular network underlying GPER1 activation in MM. Previous studies indicated the presence, in the GPER1 promoter, of binding sites for Sp1 [ 36 ], an oncogenic transcription factor highly expressed in MM [ 37 ]. To confirm Sp1 binding to GPER1 promoter in MM cells, we carried out a ChIP assay using Sp1 antibodies in the presence of G-1 or a vehicle, which confirmed the binding of Sp1 to GPER promoter, conversely reduced after G-1 treatment ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…We next investigated the molecular network underlying GPER1 activation in MM. Previous studies indicated the presence, in the GPER1 promoter, of binding sites for Sp1 [ 36 ], an oncogenic transcription factor highly expressed in MM [ 37 ]. To confirm Sp1 binding to GPER1 promoter in MM cells, we carried out a ChIP assay using Sp1 antibodies in the presence of G-1 or a vehicle, which confirmed the binding of Sp1 to GPER promoter, conversely reduced after G-1 treatment ( Figure 4 A).…”
Section: Resultsmentioning
confidence: 99%
“…The relationship between glucocorticoids such as dexamethasone and estrogen receptor signaling is less clear, with most studies showing an ability of DEX to inhibit downstream signaling without direct effects on receptor expression [ 36 , 37 ]. Previous work in prostate cancer cells similarly showed DHT-induced suppression of GPER that occurs through androgen receptor binding to transcription factors Sp1 and Sp3 and prevent their transcription of GPER [ 38 , 39 ]. Reciprocal interference between the gene transcription outputs for estrogen versus androgen is also demonstrated in breast cancer [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between glucocorticoids such as dexamethasone and estrogen receptor signaling is less clear, with most studies showing an ability of DEX to inhibit downstream signaling without direct effects on receptor expression [22,23]. Previous work in prostate cancer cells similarly showed DHT-induced suppression of GPER that occurs through androgen receptor binding to transcription factors Sp1 and Sp3 and prevent their transcription of GPER [24,25]. This decrease in receptor mRNA most likely lessens the beneficial effects of estrogen on cardiovascular function.…”
Section: Discussionmentioning
confidence: 99%